Is nurses’ clinical competence associated with their moral identity and injury? - Teng, Yue (Nursing ethics, 2024)
BackgroundThe enhancement of nursing care quality is closely related to the clinical competence of nurses, making it a crucial component within health systems.ObjectiveThe present study investigated the relationship between nurses’ clinical competence, moral identity, and moral injury during the COVID-19 outbreak.Research designThis cross-sectional study was carried out among frontline nurses, using the Moral Identity Questionnaire (MIQ), the Moral Injury Symptom Scale-Healthcare Professionals version (MISS-HP), and the Competency Inventory for Registered Nurse (CIRN) as data collection tools.Participantsand research context: The research population for this study consisted of all frontline nurses (n = 251) employed in a hospital in southern Iran. Sampling was conducted between May 1, 2021 and September 30, 2021, during the COVID-19 outbreak.Ethical considerationsThe present study received approval from the research ethics committee of Rafsanjan University of Medical Sciences, with project No. 99267 and code of ethics ID No. IR. RUMS.REC.1399.262, dated 15.02.2021.ResultsAccording to the study findings, 42.2% of the nurses demonstrated high clinical competence, while 51.4% exhibited moderate clinical competence. The results indicated a positive correlation between moral identity and clinical competence but a negative correlation between moral injury and clinical competence. Furthermore, the variables of moral identity and moral injury were found to predict 10% of the variance in clinical competence.ConclusionAccording to the results, moral identity and moral injury had an impact on the clinical competence of nurses. Therefore, implementing a program aimed at enhancing moral identity and providing training strategies to address moral injury during crises like the COVID-19 pandemic can lead to improvements in nurses’ clinical competence and the overall quality of care they provide.